ased violence before and during the COVID-19 pandemic Factors, shapes, and outcomes - الجوراني نبال (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
This study aims to identify the situation of women who are abused by their husbands, the causes of this violence, and its forms before and in light of the Covid-19 pandemic (Corona). To achieve this purpose of the study, a deliberate sample of abused women was selected, and an interview was conducted with them, the ages of the respondents ranged between 65-29 years. The study sample consisted of (10) women of different educational levels and social statuses living in the city and countryside of Lattakia. By analyzing the answers of the respondents, it became clear to me the extent of violence that a woman is subjected to by her husband, this violence that is not limited to verbal or moral violence, but extends to major physical and psychological violence. The interviews also showed an increase in the phenomenon of violence during the Covid-19 pandemic due to the presence of family members together for long periods in one place, in addition to the narrow living conditions, which led to the husband’s mastery of all forms of violence against the wife.